HUMAN CAPITAL EFFICIENCY AND FIRM VALUE USING PANEL REGRESSION - OBIORA PETERS, EMEKA; FRANKLINE C.S.A, OKEKE; IFEOMA GLORIA, DR. DURUZOR; LINUS, ADAMAA. (International Journal of Multidisciplinary Research and Studies, 2022)
This study evaluated human capital efficiency and firm value of quoted Non-financial firms in Nigeria. Its core objective is to evaluate the effect human capital efficiency has on firm values. The study employed secondary data and panel regression models which were subjected to descriptive Statistics, Correlation Matrix, and Hausman test for interpretations. Data was collected from (76) quoted Non-financial firms from the year (2011-2020). The study was anchored in Resource-based theory. Findings hold that there is a negative influence of capital employed efficiency as it has positive but not significant influence, firm size (FISZ) has negative and significant influence and firm age (FIRA) has positive and non-significant influence on firm value of non-financial firms in Nigeria. Concluding, only human capital employed efficiency and firm age influenced firm value positively and thus the study recommends that the human capital component of intellectual capital should be trained and educated regularly to build capacity. Firms’ specific growth and sustainability policy should be strongly placed using corporate governance code and other enhanced internal innovative processes to ensure that their existence is not affected by age.